2018
DOI: 10.1001/jamasurg.2017.5568
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Affordable Care Act Medicaid Expansion With Access to and Quality of Care for Surgical Conditions

Abstract: IMPORTANCE Lack of insurance coverage has been associated with delays in seeking care, more complicated diseases at the time of diagnosis, and decreased likelihood of receiving optimal surgical care. The Patient Protection and Affordable Care Act's (ACA) Medicaid expansion has increased coverage among millions of low-income Americans, but its effect on care for common surgical conditions remains unknown. OBJECTIVE To evaluate the association of the ACA's Medicaid expansion with access to timely and recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 43 publications
2
87
0
Order By: Relevance
“…The difference-in-differences approach has been used in other studies examining the effect of the Medicaid expansion. [17,43] This design estimates the effect of a policy change by comparing the change in an outcome for an affected population to the change in outcomes for an unaffected population. The design controls for baseline differences between the two groups as well as changing demographics to estimate the independent effect of the policy change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference-in-differences approach has been used in other studies examining the effect of the Medicaid expansion. [17,43] This design estimates the effect of a policy change by comparing the change in an outcome for an affected population to the change in outcomes for an unaffected population. The design controls for baseline differences between the two groups as well as changing demographics to estimate the independent effect of the policy change.…”
Section: Methodsmentioning
confidence: 99%
“…after AMI that we identified adds to a growing body of literature that has shown some improvements in care from the inpatient to outpatient settings after the Medicaid expansion. [15,17,18,43] It is possible that the Medicaid expansion affected the outpatient environment, [15,17,18,43,[47][48][49] such as through increased access to follow-up care for AMI patients, which prevented the need for readmission. These findings suggest that for Medicaid and uninsured patients, who tend to have higher readmission rates after AMI relative to privately insured patients, expanding Medicaid eligibility may mitigate these risks.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 31 states and Washington DC expanded eligibility to all nonpregnant adults with incomes of ≤138% federal poverty level (FPL) by 2018. Many quasi-experimental studies have shown that the expansion improved a broad range of access, 13−18 quality of care, 14,15,19 and clinical outcomes 20−27 among low-income adults. However, studies on people with diabetes have either relied on descriptive techniques that do not adjust for secular trends, 28,29 focused on general health access, 30 analyzed data limited to 2016, 31,32 or omitted outcomes such as treatment.…”
mentioning
confidence: 99%
“…16 But much of the debate at the state level since the 2016 election has shifted away from whether to expand Medicaid to what alternative approaches to take within the program. This article explores several new approaches (implemented or proposed) in Medicaid, using a novel survey of three Midwestern states.…”
mentioning
confidence: 99%